Resistance to the "last resort" antibiotic colistin: a single-zinc mechanism for phosphointermediate formation in MCR enzymes. Issue 50 (20th May 2020) - Lythell, Emily; Suardíaz, Reynier; Hinchliffe, Philip; Hanpaibool, Chonnikan; Visitsatthawong, Surawit; Oliveira, A. Sofia F.; Lang, Eric J. M.; Surawatanawong, Panida; Lee, Vannajan Sanghiran; Rungrotmongkol, Thanyada; Fey, Natalie; Spencer, James; et al.
Abstract : Simulations show the mono-zinc form of MCR to be stable and competent for covalent phospho(ethanolamine) intermediate formation. Abstract : MCR (mobile colistin resistance) enzymes catalyse phosphoethanolamine (PEA) addition to bacterial lipid A, threatening the "last-resort" antibiotic colistin. Molecular dynamics and density functional theory simulations indicate that monozinc MCR supports PEA transfer to the Thr285 acceptor, positioning MCR as a mono- rather than multinuclear member of the alkaline phosphatase superfamily.